The Art of Teaching Computer Science: Niklaus Wirth. - Severance, Charles (Computer (00189162), 2012)
With a goal of improving how computer science is taught, Niklaus Wirth created some of the field's most influential programming languages, including Pascal, Modula, and Oberon. An audio recording of author Charles Severance's Computing Conversations column is available at http://youtu.be/Wel2b93LjhY. In it, he discusses his interview with Niklaus Wirth, creator of some of the fieldís integral programming languages, including Modula, Pascal, and Oberon. A video interview with Niklaus Wirth is available at http://youtu.be/BJIqHIYSDrk. Wirth created some of the field's integral programming languages, including Modula, Pascal, and Oberon, with a goal of improving how computer science is taught.